Ethical design of social simulations - Almada, Marco; Attux, Romis (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2018: Anais do III Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2018.3471, 2018)
Computer simulations of social phenomena are used in academic and non-academic contexts as tools for decision-aiding. By combining social scientific knowledge, computational power, and large data sets, those systems may be involved in decisions that affect people who are not even aware of the existence of a simulation. This paper reviews topics from the philosophy of technology and computer ethics literatures in order to identify salient ethical issues related to computer simulations and the steps on the software design cycle on which they can be addressed, offering a checklist that can guide how the ethical concerns of stakeholders are listened to and incorporated into the proposed simulation system.